SOMEBODY CALL 9-1-1: HYPOTHYROIDISM MIMICKING WELLENS SYNDROME - Mathews, Gerard Jason; Subramanian, Seetha Devi; Yee, Teh When; Mathews, Joel; Abdullah, Noor Rafhati Adyani; Ismail, Shartiyah; Merican, Nor Shaffinaz Yusoff Azmi; Kartikesan, Dharmaraj (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Wellens syndrome is characterized by a distinctive pattern of electrocardiographic (ECG) pattern, specifically deep symmetrical inverted T-waves or biphasic T-waves in leads V2-V3. This condition is highly indicative of critical stenosis in the left anterior descending artery (LAD) which poses a significant risk of mortality, hence its nickname "widow maker." CASE A 38-year-old police officer was under Endocrine clinic follow-up for Graves’ disease. He underwent radioactive iodine (RAI) treatment in June 2022 and subsequently did not require thyroxine replacement for 1 year as he was clinically and biochemically euthyroid. During a clinic review in August 2023, he reported symptoms of cold intolerance, weight gain and reduced effort tolerance which hindered his ability to do his daily work. Blood investigation showed a free T4 of 7 pmol/L, and TSH was 13.6 m IU/L. The patient was diagnosed with overt hypothyroidism and was given thyroxine replacement. Electrocardiogram (ECG) done revealed deep symmetrical T-wave inversions in leads V2-V5, indicative of Wellens Type B pattern, which carries a 97% specificity for LAD occlusion. The patient was referred to cardiology service and underwent r an early coronary angiogram, which surprisingly revealed normal coronaries. Additionally, he did not exhibit any features of common Wellen mimics such as pulmonary embolism, pancreatitis, heart failure or acute stroke. He denied consuming alcohol or using any illegal stimulant substances. Blood analysis done revealed normal electrolytes. Patient was initiated on treatment with 12.5 mcg of L-Thyroxine tablets daily, with the dose topped up every 4 to 6 weeks. Upon subsequent clinic reviews, patient's initial symptoms have resolved, enabling him to resume his job without any difficulties. CONCLUSION This case highlights overt hypothyroidism as a mimicker of Wellens Syndrome. After promptly excluding critical coronary artery disease, it is imperative to evaluate and treat other potential causes of Wellens Syndrome or its mimics.